Relation between different variables of vertical jumps and sprints in Brazilian professional soccer players - Braz, T. V.; Nogueira, W. J.; Cruz, W. A.; Businari, G. B.; Ornelas, F.; Brigatto, F. A.; Germano, M. D.; Sindorf, M. A. G.; Silva, J. F.; Pellegrinotti, I. L.; Lopes C. R. (Journal of Exercise Physiology online, 2017)
The purpose of this study was to investigate the relation between different variables of vertical jumps and sprints in professional soccer players. The study consisted of 25 Brazilian elite soccer players (28.1 ± 1 yrs, 78.2 ± 6.8 kg, 1.81 ± 0.12 m, % Fat = 14.2 ± 3.2) who were ran the 10 m (S10m) and 20 m (S20m) sprint tests with change of direction at 40 m (20 + 20 m) (Acyclic Sprint) and the Zig-Zag sprint (ZZT) as well as Squat Jumps (SJ) and Counter Movement Jumps (CMJ). The Pearson`s linear correlation and the stepwise linear regression model were used to investigate both the relation and the prediction between variables. All the correlations between the variables were significant (P<0.05). The correlation magnitude between S10m-S20m (r=0.83, P<0.0001), SJ-CMJ (r=0.86, P<0.0001), and ZZT-Acyclic Sprint (r=0.79, P<0.0001) were very large. The S20m variable explained 68% (P=0.002) of the performance in S10m (P=0.001), CMJ explained additional 7%, and ZZT, 4%. The S10m variable explained 68% (P=0.001) and ZZT explained additional 9% (P=0.001) of S20m. The CMJ was the only explanatory variable (74%) for SJ (P=0.001) with additional 5% at S10m. The Acyclic Sprint explained 62% (P=0.001) of ZZT with additional 10% at S10m and S20m (P=0.001). It was concluded that the S10m-S20m, CMJ-SJ, and ZZT-Acyclic Sprint relations in the analyzed sample have dependent attributes between each other. The CMJ and SJ did not help in explaining the ZZT and the Acyclic Sprint; whereas, the S10m and S20m had low explanatory power for sprints with change of direction.